Las lenguas célticas en la investigación: cuatro observaciones metodológicas - Bernardo Stempel, Patrizia de (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2006)
The article aims at correcting some preconceived ideas often interfering with linguistic investigations concerning the Celtic languages. The following conclusions are drawn: 1) Not the unreliable population censuses, but only a consistent and varied literary production warrants the survival of a language. 2) By applying the diachronic perspective to the modern Celtic languages it is possible to account for all their peculiar morphosyntactic features, which are in part Indo-European archaisms and in part innovations typical of spoken language. 3) Before the contacts between their speakers came to an end, the so-called Celtic languages went through at least five stages of shared innovations, which are here illustrated [table 1] by listing their main isoglosses. 4) Many etymologies have to be corrected for not taking into account the historical phonology of the Celtic languages (CIb. Belaisca), their word formation (PNN Elanus et sim.), the chronology of their attestations (MlIr. adarc), their semantics (OIr. ander cannot be a Basque loanword), the different stages Celtic languages went through (CIb. gabi-).